2017
DOI: 10.1186/s12913-017-2763-5
|View full text |Cite
|
Sign up to set email alerts
|

Health workers’ perceptions of private-not-for-profit health facilities’ organizational culture and its influence on retention in Uganda

Abstract: BackgroundAn in-depth understanding of how organizational culture is experienced by health workers (HWs), and influences their decisions to leave their jobs is a fundamental, yet under-examined, basis for forming effective retention strategies. This research examined HWs’ working experiences and perceptions of organisational culture within private-not-for-profit, largely mission-based hospitals, and how this influenced retention.MethodsThirty-two HWs, including managers, in 19 health facilities in Uganda were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…Hence our findings may not be generalizable to all HCWs in Uganda particularly those with experience of managing COVID-19. It should be noted however, that the PNFP health sector is an integral part of Uganda’s healthcare system, employing about 35% of the country’s HCWs and accounting for more than 40% of the health sector outputs [ 53 ]. Also, management of COVID-19 in Uganda was restricted to a few select hospitals at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence our findings may not be generalizable to all HCWs in Uganda particularly those with experience of managing COVID-19. It should be noted however, that the PNFP health sector is an integral part of Uganda’s healthcare system, employing about 35% of the country’s HCWs and accounting for more than 40% of the health sector outputs [ 53 ]. Also, management of COVID-19 in Uganda was restricted to a few select hospitals at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation may be that study participants were HCWs in community PNFP hospitals and that, therefore, the findings may not be generalizable to HCWs employed in non-PNFP facilities in Uganda. It is worth noting, however, that the PNFP health sector employs one-third of Uganda’s HCWs [ 48 ]. Moreover, we have no reason to believe that HWCs in PNFP facilities differ significantly from their colleagues in non-PNFP settings with regard to education, experience, and other factors that may influence KAPs towards COVID-19.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Furthermore, they should provide a supportive work environment for employees living with HIV and AIDS, design policies with other stakeholders and employees to provide input on issues of when an employee is said to be too sick to work. Shumba, Kielmann and Witter ( 2017 ) exposed that professional and social divisions were found to be the source of conflict between health workers and facility management. These conflicts were characterised by undesirable reactions articulated towards governance and management.…”
Section: Methodsmentioning
confidence: 99%
“…Nurses felt to be lacking trust and confidence in management. Shumba et al’s ( 2017 ) study revealed that respondents felt little communication, and if it happened it occurred poorly. Support interventions ought to be characterised by a trusting relationship, reduced power imbalances for nursing personnel not to feel threatened by organisational protocols, to develop climate for teamwork with common values and a vision of providing active support to nurses living with and caring for PLWH.…”
Section: Methodsmentioning
confidence: 99%